Deficits in N-Methyl-D-Aspartate Receptor Function and Synaptic Plasticity in Hippocampal CA1 in APP/PS1 Mouse Model of Alzheimer’s Disease - Xu, Le; Zhou, Yiying; Hu, Linbo; Jiang, Hongde; Dong, Yibei; Shen, Haowei; Lou, Zhongze; Yang, Siyu; Ji, Yunxin; Ruan, Liemin; Zhang, Xiaoqin (Frontiers in Aging Neuroscience, 2021)
The N-methyl-D-aspartate receptor (NMDAR) is a critical molecule for synaptic plasticity and cognitive function. Impaired synaptic plasticity is thought to contribute to the cognitive impairment associated with Alzheimer's disease (AD). However, the neuropathophysiological alterations of NMDAR function and synaptic plasticity in hippocampal CA1 in transgenic rodent models of AD are still unclear. In the present study, APP/PS1 mice were utilized as a transgenic model of AD, which exhibited progressive cognitive impairment including defective working memory, recognition memory and spatial memory starting at 6 months of age and more severe by 8 months of age. We found an impaired long-term potentiation (LTP) and reduced NMDAR-mediated spontaneous excitatory postsynaptic currents (sEPSCs) in the hippocampal CA1 of APP/PS1 mice with 8 months of age. Golgi staining revealed that dendrites of pyramidal neurons had shorter length, less intersections and lower spine density in APP/PS1 mice comparing to control mice. Further, the reduced expression levels of NMDAR subunits, PSD95 and SNAP25 were observed in hippocampus of APP/PS1 mice. These results suggest that NMDAR dysfunction, impaired synaptic plasticity and disrupted neuronal morphology constitute an important part of the neuropathophysiological alterations associated with cognitive impairment in APP/PS1 mice.